Environmental Health Intelligence New Zealand (EHINZ): intelligence for public health action. - Borman B; Haenfling C; Kowalik-Tait A; Hipgrave P (Springer Nature, 2022)
The New Zealand health system is data-rich, information-poor, and intelligence meagre. However, there is widespread confusion about the definitions of these terms, so they are often used synonymously. Like many jurisdictions, we continue to collect and collate vast quantities of data at an increasing rate. Many tools are available to “analyse” the data deluge with the false expectation that “intelligence” will be produced. Naively, such a data-driven, machine-analysed paradigm is often thought to produce the “evidence” for decision-making and policy development. Continuing such a blinded approach poses potential health risks to New Zealanders and remains a major impediment to improving our health status Creating intelligence from information involves humans (perhaps in concert with AI) utilising their interpretative abilities, asking the “so what, “what does it mean” questions, and employing their communication skills to disseminate the answers. To move from information to intelligence requires agencies to employ, develop and maintain a sufficiently skilled workforce over a long period, rather than the quick and easy investment in more and faster machines and software. Only through a human-driven evaluation of intelligence-based decisions and policies will our knowledge about the environmental health system increase and ultimately yield better health outcomes. Environmental Health Intelligence NZ (EHINZ) provides intelligence as evidence for decision-making and policy development in environmental health. It is based on the interpretation, communication, and dissemination of information from the surveillance more than seventy environmental health indicators (EHIs) across twelve domains (e.g., air and water quality, climate change), exposure to hazardous substances, and social vulnerability indicators to environmental hazards (e.g., flooding, climate change, sea-level rise, wildfires, heat waves). The paper details our approach, with two case studies, in providing the NZ health system with “intelligence for environmental health decisions.”
Keywords: Epidemiology; Health indicators; Health intelligence; Spatial analysis